RESPON PERTUMBUHAN DAN PRODUKSI KACANG HIJAU (VIGNA RADIATA L.) TERHADAP PERLAKUAN PERBEDAAN NAUNGAN - Dewa Oka Suparwata (Akademika, 2018)
This research aimed to study the respond of the growth and production of green beans toward shade treatment. The research location is in Pentadio Timur, Telaga Biru Gorontalo, which was done for 3 months from Desember 2016 to Februari 2017. The research design is RAK or group randomized design, with four level of treatment, which is, P0 = without shade, P1 = 1 layer of paranet thickness treatment, P2 = 2 layer of paranet thickness treatment, P3 = 3 layer of paranet thickness treatment. These four treatments was repeated 3 times that obtains 12 trial plots. The data were analyzed through Anova with SAS data processing. The result of variant investigation analysis on BNT (P